Unjust Divergence in Earnings in Germany? - Stefan Liebig; Jürgen Schupp (Weekly Report, 2005)
Since a court decided that bonuses paid to the former top management at Mannesmann AG were unjustifiable there has been widespread public discussion over fair pay in Germany. This has been against the background of big increases in the salaries paid to top executives at a time when the economy is sluggish and there is high unemployment. A special survey by the Socio-Economic Panel (SOEP) conducted by DIW Berlin in conjunction with Infratest Sozialforschung showed that many people feel top executives are too highly paid, and that the differences between their earnings and those of unskilled workers is not justifiable. Many, especially in eastern Germany, also feel that their own pay is unfairly low. Greater transparency would increase the acceptance of differentials that are otherwise seen as unjust.
Keywords: 330